Guidance on the requirements for the development of microbiological criteria. (13th November 2017) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Fernández Escámez, Pablo Salvador; Girones, Rosina; Herman, Lieve; Koutsoumanis, Konstantinos; Lindqvist, Roland; Robertson, Lucy; et al.
Abstract: The European Food Safety Authority asked the Panel on Biological Hazards (BIOHAZ) to deliver a scientific opinion providing: (i) a review of the approaches used by the BIOHAZ Panel to address requests from risk managers to suggest the establishment of microbiological criteria; (ii) guidance on the required scientific evidence, data and methods/tools necessary for considering the development of microbiological criteria for pathogenic microorganisms and indicator microorganisms; (iii) recommendations on methods/tools to design microbiological criteria and (iv) guidelines for the requirements and tasks of risk assessors, compared to risk managers, in relation to microbiological criteria. This document provides guidance on approaches when: (i) a quantitative microbial risk assessment (QMRA) is available, (ii) prevalence and concentration data are available, but not a QMRA model, and (iii) neither a QMRA nor prevalence and/or concentration data are available. The role of risk assessors should be focused on assessing the impact of different microbiological criteria on public health and on product compliance. It is the task of the risk managers to: (1) formulate unambiguous questions, preferably in consultation with risk assessors, (2) decide on the establishment of a microbiological criterion, or target in primary production sectors, and to formulate the specific intended purpose for using such criteria, (3) consider the uncertainties in impact assessments on public health and on product compliance and (4) decide the point in the food chain where the microbiological criteria are intended to be applied and decide on the actions which should be taken in case of non‐compliance. It is the task of the risk assessors to support risk managers to ensure that questions are formulated in a way that a precise answer can be given, if sufficient information is available, and to ensure clear and unambiguous answers, including the assessment of uncertainties, based on available scientific evidence.